2018
DOI: 10.1080/03639045.2017.1421661
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and statistical optimization of intravenous temozolomide-loaded PEGylated liposomes to treat glioblastoma multiforme by three-level factorial design

Abstract: The aim of the presented study was to develop PEGylated liposomes of Temozolomide (TMZ) that provide optimum drug concentration at tumor site. Reverse phase evaporation (REV) method was used to prepare TMZ-loaded PEGylated liposomes. Formulation was optimized by using design expert software by 3 factorial design. The physicochemical properties including size, morphology, entrapment efficiency, drug loading, etc. of formulated liposomes were evaluated. Finally, the optimized formulation was selected for in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…Vanza et al encapsulated TMZ in a PEGylated liposome made of soybean phosphatidylcholine (PC), dipalmitoyl phosphatidylcholine (DPPC), dipalmitoyl phosphatidylcholine-sodium (DPPG), egg lecithin, cholesterol, and 1,2-distearoyl-phosphatidylethanolamine-methyl-polyethyleneglycol conjugate-2000 (Na + salt) [2]. The results revealed a prolonged release of TMZ from PEGylated liposomes up to 800 min, as compared with free TMZ, which was released in 90 min, according to in vitro studies.…”
Section: Stealth Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanza et al encapsulated TMZ in a PEGylated liposome made of soybean phosphatidylcholine (PC), dipalmitoyl phosphatidylcholine (DPPC), dipalmitoyl phosphatidylcholine-sodium (DPPG), egg lecithin, cholesterol, and 1,2-distearoyl-phosphatidylethanolamine-methyl-polyethyleneglycol conjugate-2000 (Na + salt) [2]. The results revealed a prolonged release of TMZ from PEGylated liposomes up to 800 min, as compared with free TMZ, which was released in 90 min, according to in vitro studies.…”
Section: Stealth Liposomesmentioning
confidence: 99%
“…In 2016, 330,000 new patients were diagnosed, while the death toll from CNS tumors reached 227,000 [1]. GBM is the most aggressive form of brain cancer, is incurable and has an average survival rate of 12 months [2]. The main challenges raised by this disease are its high degree of genetic and phenotypic heterogeneity, the blood brain barrier, its increased resistance to therapies, and the existence of cancer stem cells [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles have been shown to reduce the systemic toxicity of chemotherapeutic agents, to improve their pharmacokinetics and enhance their selective accumulation in the tumor site. [46][47][48][49][50][51] Polymeric nanoparticles (PNPs) are considered to be the most promising alternative to lipid-based carriers for the delivery of chemotherapeutic agents to the brain. PNPs include poly-(alkyl cyanoacrylate) (PACA), poly-(l-glutamic acid) poly (lactide-co-glycolide, PLGA), polylactide (PLA), polyethyleneimine (PEI), N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer, poly(ethylene glycol) (PEG), dextran, and chitosan.…”
Section: Chemotherapeutic Deliverymentioning
confidence: 99%
“…It has been demonstrated that the currently limited efficacy of convection-enhanced delivery (CED) could be enhanced by a liposomal formulation, thus achieving enhanced TMZ localization to the tumor site with minimal toxicity. On the other hand, a novel approach has been described for treating GBM by CED of (PEGylated) liposomes containing TMZ, the known chemotherapeutic agent (Vanza et al, 2018;Lin et al, 2018.;Nordling-David et al, 2017). However, to our knowledge no magnetic targeting of temozolomide is ever presented in the literature.…”
Section: Surface Coating Of Magnetic Nanoparticlesmentioning
confidence: 99%